Clinical Profile of Patients with Polycystic Ovary Syndrome at Tertiary Care Hospital - Seema Rafiq, Sofia Shah, Asia Asghar, (Pakistan Journal of Medical & Health Sciences, 2023)
Polycystic ovary syndrome, with an incidence of up to 10%, is one of the communal causes of anovulation in females of reproductive age. Diagnostic criteria for PCOS include enlarged polycystic ovaries, obesity, hirsutism, and oligomenorrhea. These women are more susceptible to endometrial cancer, type II diabetes, dyslipidemia and premature atherosclerosis. Objective: The aim of this study was to determine the different clinical profiles of PCOS patients and to educate patients about the long-term outcomes related with this condition. Methods: This cross-sectional study was conducted at the obstetrics and gynaecology department of Ayub Teaching Hospital, Abbottabad for the duration from 1st January 2019 to 31st December 2019. The study included 110 people with oligomenorrhea, obesity, acne, infertility and hirsutism. Young women who had their menarche less than two years ago, women over 45 years of age, and patients receiving exogenous estrogen or progesterone therapy were excluded from the study. For the social sciences, data was entered and analyzed with SPSS 25.0. The percentages and mean values were determined for several parameters. Results: Of the 110 patients selected for this study, 46 (41.8%) were married and 64 (58.2%) were unmarried. In contrast to rural areas, there were more patients from urban areas (63.6% vs 36.4%). 6.4% of patients were underweight, 20% and 59.1% were overweight and obese. Most patients (71.8%) had oligomenorrhea or amenorrhea. 70% of patients gained weight, many of whom attributed this to menstrual problems. Infertility affected 30% of married patients. Hirsutism and acne were found in 21.8% and 25.5%, respectively. Acanthosis Nigricans, a manifestation of insulin resistance, was found in 31.8% of patients. Eight patients were taking medication for hyperprolactinemia, ten women (10%) had type 2 diabetes taking oral hypoglycemics for glycemic control, and six had hypertension. All patients underwent USG and 85 (77.3%) of them showed a characteristic necklace pattern of follicular arrangement. Conclusion: Using clinical features and ultrasonography in women, PCOS can be accurately diagnosed using the Rotterdam criteria. The two main findings we observed in our patients were weight gain and amenorrhea or oligomenorrhea. It is very important to inform and educate unmarried patients with PCOS about the relationship of this condition with infertility and chronic health problems. Keywords: Oligomenorrhea, PCOS, Anovulation and obesity